Oral administration of a casein matrix containing β-casofensin protects the intestinal barrier in two preclinical models of gut diseases. (December 2016) - Bessette, Claudine; Henry, Gwénaële; Sekkal, Soraya; Benoit, Bérengère; Bruno, Jérémie; Meugnier, Emmanuelle; Ferrier, Laurent; Théodorou, Vassilia; Léonil, Joelle; Plaisancié, Pascale
Highlights: β-Casofensin, a milk bioactive peptide, prevented intestinal hyperpermeability induced by neonatal stress. This effect was accompanied by preservation of the intestinal goblet cells. β-Casofensin also prevented the hyperplasia of enteroendocrine cells induced by neonatal stress. β-Casofensin maintained its effects when administered in a casein matrix. Moreover, a casein matrix with β-casofensin protected against indomethacin-induced enteritis. Abstract: β-Casofensin is a milk-derived bioactive peptide that interacts with intestinal goblet cells. We aimed to determine whether β-casofensin could prevent intestinal dysfunctions induced by neonatal maternal separation (NMS) and whether it retains its protective effects when administered in a casein matrix. We also evaluated whether a casein matrix enriched in β-casofensin protects against intestinal enteritis induced by indomethacin. β-Casofensin abolished NMS-induced jejunal hyperpermeability and prevented the depletion of goblet and Paneth cells induced by NMS. In addition, β-casofensin maintained its effectiveness against NMS-induced intestinal barrier alterations when administered in a casein matrix. A casein matrix containing β-casofensin also reduced intestinal damages induced by indomethacin. A functional food containing β-casofensin may prevent both the deleterious effects of neonatal stress on the intestinal barrier and indomethacin-induced enteritis. These results suggest a promising application of β-casofensin as a gut barrier protector in the context of bioactive foods and clinical nutrition.